Effect of NPC1L1 and HMGCR Genetic Variants With Premature Triple-Vessel Coronary Disease - Zhao, Xueyan; Xu, Jingjing; Tang, Xiaofang; Huang, Keyong; Li, Jiawen; Liu, Ru; Jiang, Lin; Zhang, Yin; Wang, Dong; Sun, Kai; Xu, Bo; Zhao, Wei; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Both Niemann-Pick C1-like 1 (NPC1L1) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) play a key role on dyslipidaemia. We aim to evaluate whether NPC1L1 and HMGCR genetic vari-ants are associated with susceptibility of premature triple-vessel disease (PTVD). Methods: Four single-nucleotide polymorphisms (SNPs) (rs11763759, rs4720470, rs2072183 and rs2073547) of NPC1L1; and three SNPs (rs12916, rs2303151 and rs4629571) of HMGCR were genotyped in 872 PTVD patients (males ≤ 50 years old and females ≤ 60 years old), and 401 healthy control. Results: After adjusted for age and sex, rs12916 of HMGCR was associated with the risk of PTVD in domi-nance model (odds ratio [OR]=1.68, 95% confidence intervals [CI]: 1.29-2.18, P<0.001), recessive model (OR=1.43, 95%CI: 1.08-1.90, P=0.013) and codominant model (OR=1.38, 95%CI: 1.17-1.63, P<0.001); meanwhile, rs4720470 of NPC1L1 was related to increased risk of PTVD in recessive model (OR=1.74, 95%CI: 1.14-2.74, P=0.013). Patients who carried both variant rs4720470 and rs12916 also had the risk of PTVD (P<0.001); however, there were no correlation between these SNPs and the SNYTAX score (all P>0.05). Conclusions: This is the first report that rs4720470 is a novel polymorphism of the NPC1L1 gene associated with PTVD, and rs12916 of HMGCR gene appears to be a strong genetic marker of PTVD. Our study may improve the early warning, therapeutic strategies and drug development of PTVD.